Penentuan Interval Waktu Maintenance Forklift Terhadap Komponen Kritis Berdasarkan Data Kerusakan Mesin Menggunakan Metode Preventive Age Replacement (Studi Kasus: PT. XXX) - Gustama Putra Alhadi; Din Aswan Amran Ritonga; Junaidi Junaidi (JITEKH, 2021)
A forklift is a lifting tool that functions to move goods from one place to another, with a short distance and a certain height, this heavy equipment is very useful because it can move very heavy goods in a vertical or horizontal direction. Problems that are often especially related to damage to unit components at PT.XXX, which are composed of the main part, namely the forklift engine. Damage to this section can result in downtime and delay in the production process which results in machine performance being less effective and efficient. Effectiveness in the production process requires the right strategy to keep the machine in operation by determining the optimal maintenance time interval using the criticality analysis method. After calculating with the criticality analysis method, it is found that the components of the hydraulic system and transmission are critical components. Furthermore, preventive replacement measures for hydraulic system components can be taken after 6800 hours of operation. The transmission component can also be done after operating for 900 hours or during an overhaul. While the inspection action for hydraulic system components is carried out after operating for 620.76 hours, the transmission component is carried out after operating for 540.39 hours. After checking and inspection, the avaibility value of the two components is above 95%, which means that the inspection can increase availability and prevent downtime in the unit and optimize the production process.